RETRACTED: Determining the optimal placement scheme and height of elements that accelerate heat exchange processes in solar air heater collectors through mathematical modeling - Kuchkarov Akmal; Uzbekov Mirsoli; Boynazarov Bekzod; Abdukarimov Bekzod; Mamatov Olmosbek; Muminov Shermuhammad (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001